Swan in the Grail - Holloway, Sue (GaiaQuest, 1999)
Keywords: Ethics; Swans; Ecofeminism; dept.wgs; faculty_collection

Eves journey: feminine images in hebraic literary tradition. - Holloway, Sue (Anthropology of Consciousness, 1991)
Nehama Aschkenasy Eves Journey: Feminine Images in Hebraic Literary Tradition Philadelphia: University of Pennsylvania Press, 1986. ISBN 0‐8122‐8033‐4. Hardcover, $36.95. Pp. xv+269. Copyright © 1991, Wiley Blackwell. All rights reserved
Keywords: dept.wms